Assessing significance in genome-wide studies - Evans, David (Henry Stewart Talks, 2008)
Hypothesis testing, Ruling out artefactual associations, Asymptotic P values and problems with interpretation, Multiple testing and Bonferroni corrections, Permutation, pointwise and genomewise significance, Bayes factors, Comparison between P values and Bayes factors, Replication studies